The risk of COVID-19 in patients with bullous pemphigoid and pemphigus: A population-based cohort study - Kridin, Khalaf (J Am Acad Dermatol, 2021)
BACKGROUND: The burden of COVID-19 in patients with bullous pemphigoid (BP) and pemphigus is yet to be evaluated. OBJECTIVE: To assess the risks of COVID-19 and COVID-19-associated hospitalization and mortality in patients with BP and pemphigus and to delineate determinants of severe COVID-19 illness among these patients. METHODS: A population-based cohort study compared COVID-19 and its complications in patients with BP (n = 1845) and pemphigus (n = 1236) with age-, sex-, and ethnicity-matched control subjects. RESULTS: The risks of COVID-19 (hazard rate [HR], 1.12; 95% confidence interval [CI], 0.72-1.73; P = .691) and COVID-19-associated hospitalization (HR, 1.58; 95% CI, 0.84-2.98; P = .160) was comparable between patients with BP and controls. The risk of COVID-19-associated mortality was higher among patients with BP (HR, 2.82; 95% CI, 1.15-6.92; P = .023). The risk of COVID-19 (HR, 0.81; 95% CI, 0.44-1.49; P = .496), COVID-19-associated hospitalization (HR, 1.41; 95% CI, 0.53-3.76; P = .499), and COVID-19-associated mortality (HR, 1.33; 95% CI, 0.15-11.92; P = .789) was similar in patients with pemphigus and their controls. Systemic corticosteroids and immunosuppressants did not predispose COVID-19-positive BP and pemphigus patients to a more severe illness. LIMITATIONS: Retrospective data collection. CONCLUSIONS: Patients with BP experience increased COVID-19-associated mortality and should be monitored closely. Maintaining systemic corticosteroids and immunosuppressive adjuvant agents during the pandemic is not associated with worse outcomes.